Carcass characteristics, meat quality, feeding behavior of Nelore heifers fed diets containing sunflower pie - Alves, Karine Regina; Silva, Leandro das Dores Ferreira da; Ribeiro, Edson Luís Azambuja; Guerra, Geisi Loures; Paiva, Fernando Henrique Pereira de; Henz, Éderson Luis (Acta Scientiarum. Animal Sciences, 2016)
The aim was to evaluate the feeding behavior, carcass characteristics and meat quality of Nelore heifers fed sunflower pie replacing cottonseed meal. They were used 30 heifers with average initial weight of 274 kg ± 28 kg and average age of 24 months, confined for 76 days. The design was completely randomized with five treatments (0, 150, 300, 450 and 600 g kg-1 DM) and six replicates per treatment. By completing 24 hours after slaughter, it evaluated muscle conformation and degree of finish made the longissimus dorsi at the 13th rib. A representative sample between the 10th and 12th ribs was collected for evaluation of the physical components of carcasses. As well as the other variables, the hot carcass weight, dressing percentage, carcass length and rib eye area were not influenced by different pie levels in feed. The mean percentage of muscle, bone and fat from the carcass were 53.45; 16.14 and 29.46%, respectively, similar among treatments. Therefore, the use of up to 600 g kg-1 of sunflower pie replacing cottonseed meal as the main protein source, did not affect the carcass characteristics and meat quality of Nelore heifers.